The Power of Inevitability: How OpenAI Configures the Future - Nieborg, David; Karppi, Tero; boyd, danah (AoIR Selected Papers of Internet Research, 2026)
This paper investigates the discursive strategies employed by OpenAI, the creators of ChatGPT, to position themselves as leading the development of Artificial General Intelligence (AGI). Through an examination of 44 texts, including OpenAI’s corporate communications, media appearances, and journalistic coverage, this study reveals how OpenAI utilizes socio-political anxieties and Silicon Valley ideals to shape a discourse of inevitability about AGI’s future. OpenAI’s discourse centers on four key areas: national security concerns, the juxtaposition of "freedom" and "openness" against the threat of superintelligence, the company’s shift from non-profit to commercial entity, and the promotion of AI as a solution to global problems. By strategically invoking these themes, OpenAI establishes itself as a "technological solution." The company’s rhetoric emphasizes the need for regulation, while simultaneously positioning itself as the authority on AI governance. OpenAI’s calls for democratic oversight are often coupled with warnings about the dangers of unchecked AI development, reinforcing the company’s role as a responsible actor in the tech sector. Ultimately, OpenAI’s discursive strategies serve to define the future of AI in a way that aligns with the company’s interests. By framing AGI as both inevitable and potentially dangerous, OpenAI creates a narrative that justifies its own pursuit of power against the global diffusion of AGI.